2008
DOI: 10.1210/me.2006-0302
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Stimulatory Factor-2 Regulates Steroidogenic Factor-1 Expression in Endometriosis

Abstract: Local estrogen biosynthesis is a major factor in the pathogenesis of endometriosis. Aberrant expression of steroidogenic acute regulatory protein (StAR) and aromatase in endometriotic tissue leads to an up-regulation of estrogen production. The transcription factor steroidogenic factor-1 (SF-1) activates the promoters of both StAR and aromatase in endometriotic tissue. We investigated differences in SF-1 expression in endometriotic tissue and normally located endometrium to elucidate the mechanism underlying i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 35 publications
3
36
1
Order By: Relevance
“…The similar results obtained in proliferative and secretory endometrial stromal cells at passages 2-3 cultured in the absence of ovarian steroids suggest the loss during culture of their characteristic regulation on endometria in vivo; then, and similarly to other authors (Vigano et al 2001, Utsunomiya et al 2008, we analyzed all data together. As it has been widely reported, the stromal cells treatment with steroids induces their differentiation to predecidual stromal cells in vitro allowing the molecule synthesis expressed during the uterine receptive window (Sugino et al 2000, White et al 2005.…”
Section: Discussionsupporting
confidence: 52%
“…The similar results obtained in proliferative and secretory endometrial stromal cells at passages 2-3 cultured in the absence of ovarian steroids suggest the loss during culture of their characteristic regulation on endometria in vivo; then, and similarly to other authors (Vigano et al 2001, Utsunomiya et al 2008, we analyzed all data together. As it has been widely reported, the stromal cells treatment with steroids induces their differentiation to predecidual stromal cells in vitro allowing the molecule synthesis expressed during the uterine receptive window (Sugino et al 2000, White et al 2005.…”
Section: Discussionsupporting
confidence: 52%
“…Some studies have suggested that methylation of the SF-1 promoter and the upregulation of stimulatory factor-2 might play important roles in SF-1 regulation. 18,19 To investigate the roles of SF-1 and StAR in endometriosis, any association between the expression levels of these proteins and the menstrual cycle and stage of endometriosis was evaluated. The results showed that the expression levels of SF-1 and StAR in ectopic endometria were significantly correlated with the stage of endometriosis; higher expression of SF-1 and StAR were observed in the early stages compared with the advanced stages of endometriosis.…”
Section: Y Tian B Kong W Zhu Et Al Sf-1 and Star Expression And Enmentioning
confidence: 99%
“…When considered together with the results of ChIP analysis, the finding suggests that reduced Fshr expression results from the direct loss of USF at the Fshr promoter. However, previous studies identify another potential mechanism involving the transcription factor SF-1 (or NR5A1), which was identified as both a target of USF and an activator of Fshr (15,(31)(32)(33). Because Sertoli cells and granulosa cells express both SF-1 and FSHR, a reduction in SF-1, due to USF loss, could be responsible for the reduction in Fshr mRNA (34,35).…”
Section: Usf Deficiency Impairs Fshr Expression In the Ovarymentioning
confidence: 99%